PENGARUH SERVANT LEADERSHIP DAN JOB SATISFACTION TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DIMEDIASI TRUST DI RSUD SAYANG CIANJUR - Husna, Shafira Dwi; Setyaningrum, Retno Purwani (JURNAL ILMIAH EDUNOMIKA, 2024)
The era of globalization is an era that has very rapid progress because there are no restrictions in accessing information so that it makes agencies must be able to evaluate and review what can be done to advance the company and the agency. This is supported by increasingly sophisticated and developing technology, the development of the times will certainly be increasingly indulgent for everyone with various layers. The purpose of this study was to determine the direct and indirect effects between servant leadership variables and job satisfaction mediated by trust on organizational citizenship behavior. This research was conducted using a quantitative approach, the respondents were health workers at Sayang Cianjur Hospital with a population of 1,413 people with a sample of 93 samples. The analysis method used in this research is Partial Least Square (PLS) using the SmartPLS version 3.0 program. The results showed that servant leadership has no effect on organizational citizenship behavior, job satisfaction has no effect on organizational citizenship behavior, trust affects organizational citizenship behavior, servant leadership has no effect on trust, job satisfaction has an effect on trust, servant leadership mediated trust has no effect on organizational citizenship behavior and job satisfaction mediated by trust affects organizational citizenship behavior